2019
DOI: 10.1096/fj.201900204rr
|View full text |Cite
|
Sign up to set email alerts
|

Original low birth weight deteriorates the hindgut epithelial barrier function in pigs at the growing stage

Abstract: The deteriorative effect of low birth weight (LBW) on the mucosal permeability of the small intestine in piglets has been widely confirmed. However, whether the hindgut epithelial barrier function in LBW pigs is deteriorated during the growing stage is still unclear. Our study investigated differences in the hindgut epithelial barrier function between LBW and normal birth weight pigs during the growing stage (d 90). Our data demonstrated that the hindgut epithelium of LBW pigs has a high histopathological scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 63 publications
2
27
0
1
Order By: Relevance
“…28 The chemical markers (endotoxin, DAO, D-lactate, and zonulin) that are usually low in the circulation system in healthy individuals will show a signicant increase in the circulation system during the destruction of the intestinal barrier. 29 Our data showed that the levels of endotoxin, DAO, D-lactate, and zonulin in plasma and colonic mucosa were signicantly decreased in the ICA group, which implied decreased intestinal permeability of the ICA piglets. Tight junctions (TJs) are the primary component of the intestinal epithelium that maintain selective permeability.…”
Section: Discussionmentioning
confidence: 57%
“…28 The chemical markers (endotoxin, DAO, D-lactate, and zonulin) that are usually low in the circulation system in healthy individuals will show a signicant increase in the circulation system during the destruction of the intestinal barrier. 29 Our data showed that the levels of endotoxin, DAO, D-lactate, and zonulin in plasma and colonic mucosa were signicantly decreased in the ICA group, which implied decreased intestinal permeability of the ICA piglets. Tight junctions (TJs) are the primary component of the intestinal epithelium that maintain selective permeability.…”
Section: Discussionmentioning
confidence: 57%
“… 18 Abnormal expression and distribution of tightly coupled complexes in intestinal epithelial cells will directly affect the intestinal barrier function and intestinal permeability, thus inducing many intestinal diseases. 19 Researchers have done a lot of work on BPA and intestinal diseases and their relationship. The effects of BPA on gut health are mainly manifested in the downregulated lysozyme expression, decreased fecal antibacterial activity, reduced secretion level of intestine immunoglobulin A (IgA), increased intestinal permeability, and the occurrence of colitis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the disturbance of their secretion or function during post-natal development in PGR induces long-term changes in tissue growth and function, with persistent detrimental effects (15). IUGR pigs were also reported to have impaired antioxidant capacity and disorder of the immune system (19, 20). The increased serum levels of proinflammatory cytokines, such as interleukin-8 (IL-8) reflects the severe inflammatory response in pigs (21, 22).…”
Section: Introductionmentioning
confidence: 99%